-43=x

Simple and best practice solution for -43=x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -43=x equation:


Simplifying
-43 = x

Solving
-43 = x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-1x' to each side of the equation.
-43 + -1x = x + -1x

Combine like terms: x + -1x = 0
-43 + -1x = 0

Add '43' to each side of the equation.
-43 + 43 + -1x = 0 + 43

Combine like terms: -43 + 43 = 0
0 + -1x = 0 + 43
-1x = 0 + 43

Combine like terms: 0 + 43 = 43
-1x = 43

Divide each side by '-1'.
x = -43

Simplifying
x = -43

See similar equations:

| -(-2a+2)=-6(3+9a) | | t-15=19 | | 25+5-10(y+4)= | | 4a+12=4a+6a | | 2x+5=3x+-1 | | 7(8+3x)=19 | | 8t+3(3t-2)=-5t-10 | | 5-2x/7=9/14 | | 5(3x-6)-3(x+1)-19x= | | 1/8+y=-7/16 | | -96=z+-83 | | 3x-3=21x+9 | | 8x+7=87 | | 4(-4y^5)= | | 3x=2x+17 | | x-1/7=13/14 | | (6x+1)(x-7)=0 | | 3z-5-z+3=0 | | 5/8x+7=-3/8x | | 14x-13/8-13x=10/8+3/8 | | -0.8x+0.5x-6=9 | | 6n^2=-8n-1 | | x-1/3=2x/5+1/15 | | x+x+15=x+45+x+40+x+25 | | 7z+10-4z=8+2z+10 | | y-13/23=-5/23 | | 6-1/2x=3/5 | | 2x-(x+2)-(x-2)=x-10 | | 2(n-3)-(4-5n)=6n | | f+-63=27 | | 5x^3-3x^2=2 | | (8x+7)(x-4)=0 |

Equations solver categories